Penguatan Karakter Religius Warga Masyarakat dalam Kegiatan Lailatul Ijtima di Desa Sinanggul 1 Mlonggo - Fitri Aulia Dewi, Maulida; Dianita, Vivi Dianita; Nailis Sa’adah, Dina; Rohman, Fathur (ASANKA : Journal of Social Science and Education, 2024)
"Lailatul Ijtima" means the night of the assembly which is held once a month. This activity started from the custom of the former scholars to regularly meet and gather with discussing a variety of issues ranging from issues of religion and also issues of integrity to nationality, the meeting was held at night time then this tradition continued in the form of the routine activities of the organization Nahdlatul Ulama under the name Lailatul Ijtima. The purpose of this activity is not only to understand and practice religious teachings, but also to understand the teachings of religion and to strengthen religious character to the community. As for the method used in the study of this activity is qualitative discreet with the technique of data collection through observation with direct involvement accompanied by documentation and active participation in following the activities. The results of the study of this activity can be concluded that the activities of the lailatul Ijtima 'or night of the congregation is very effective to generate and consolidate the relationship between the manager of Jam'iyah NU and the jamaah Nahdliyyin Village of Sinanggul 1 at the same time as an attempt to increase the amaliyah of ubudiyah among the citizens of the community of Sinangul 1 in general and the citizen of Nahdliyyiin.